Digital Transformation: Fintech Moderation on the Relationship between Intellectual Capital, Liquidity, and Credit Risk on Financial Performance - Triyono, Triyono; Andy Dwi Bayu Bawono; Angling Khrisna Adhi (Universitas Muhammadiyah Surakarta, 2026)
This study aims to examine the effect of intellectual capital, credit risk, and liquidity on financial performance, with financial technology as a moderating variable in conventional banking companies in Indonesia. This research is based on the Resource-Based View, which emphasizes the importance of managing internal resources to achieve competitive advantage. The population characteristics of conventional commercial banks listed on the Indonesia Stock Exchange during the 2020–2024 period. Using purposive sampling, 22 banks were selected, resulting in 110 observations. The data were analyzed using multiple linear regression and moderated regression analysis with EViews 12. The results indicate that intellectual capital has a positive and significant effect on financial performance, while liquidity has a negative and significant effect. Meanwhile, credit risk does not significantly affect financial performance. Furthermore, financial technology is proven to strengthen the relationship between intellectual capital and financial performance. However, financial technology is not able to moderate the relationship between credit risk and liquidity on financial performance. These findings suggest that in the digital transformation era, optimizing intellectual capital supported by financial technology is crucial in improving banking performance. This study contributes to the literature by integrating internal resources and digital transformation in explaining financial performance